Gas Concentration Measuring-System (CH4, NH3, CO2) Upon Cow Feces in an Encased-Space Based on Arduino Uno - Romdon, Mu'hamad Asfi; Hamdani, Dedy; Medriati, Rosane (Kasuari: Physics Education Journal (KPEJ), 2024)
The goal of this exploration is to fabricate an estimating instrument for perceiving Methane, Smelling salts, and Carbon Dioxide gas concentrations in cow feces within a confined space. The feasibility of gas concentration detection devices using MQ-2 sensors, MQ-4 sensors, and Arduino Uno-based MQ-135 sensors will also be tested. This research relates to physics, particularly instrument physics. The research will employ hardware design, software design, and testing methodologies. The gas used for testing was produced from 500 grams of cow feces through three treatments: no treatment, addition of 50 grams of activated charcoal, and addition of 50 milliliters of EM4. The tool validation test was conducted by three experts, and the typical worth acquired was 95.8%, classified as entirely achievable. The experiment yielded the highest concentrations of CH4, NH3, and CO2 gases at 11:30 AM (plus EM4), 03:00 AM (plus EM4), and 24:00 AM (without treatment), respectively, with readings of 9.49 ppm, 26.89 ppm, and 4.57 ppm.